APLIKASI QR CODE UNTUK EFISIENSI DAN AKSES INFORMASI UMKM DESA JANAPRIA LOMBOK TENGAH - Kukuh Tondoyekti; Mariana Mariana; Baiq Dewi Lita Andiana; Titin Windiasari (Nusantara Hasana Journal, 2025)
This community service program designs a QR code-based information system to address efficiency and information gaps for MSMEs in Janapria Village, Central Lombok. According to 2025 BPS data, Janapria is the second-largest village but holds a Desa Mandiri status, lagging behind Lekor and Saba villages which are already Desa Maju. The primary issue is the lack of systematic data tracking for its significant potential in weaving crafts and grocery shops. Through a participatory approach socialized in September 2025, QR codes are implemented as a low-cost data tool rather than a payment instrument. This system connects entrepreneurs with the village government to eliminate repetitive manual data collection and open external information channels. The program serves as a replicable model to bridge economic potential with village development.